Thinness in a population of rural girls in Poland: 14-year changes and regional differentiation. Issue 5 (7th March 2019) - Chrzanowska, Maria; ,; Suder, Agnieszka
Abstract: Worldwide data indicate a growing number of energy homeostasis disorders, which are especially dangerous in childhood. The distribution and growing trends of overweight and obesity in children have been widely investigated, unlike the prevalence of too-low body weight and its determinants. This study aimed to estimate the frequency of body mass deficiency in Polish rural girls and differences among four Polish regions – Choszczno and Leszno in the north-west, and Ostrów Mazowiecka and Suwałki in the north-east. Data were taken from 7764 rural girls aged 9–18 years examined in 1987, when the country was in economic crisis, and 9431 such girls examined in 2001, when the country was undergoing political transformation. The frequency of weight deficiency was estimated based on BMI by applying the international standards of Cole. An Extent of Overweight (EOW) index was used to create an Extent of Thinness (EOT) index. A significant increase in weight deficiency was found in the rural girls – from 7.5% in 1987 to 8.9% in 2001 – and an increase in the EOT index from 0.37 in 1987 to 0.43 in 2001. Analysis by area of residence demonstrated significant differentiation. In the regions in north-west Poland, mainly inhabited by non-farming families, the prevalence of weight deficiency in girls almost doubled from 1987 to 2001, probably because of the mass and long-term unemployment that resulted from the closure of state farms in 1992. In contrast, in the north-east regions, the prevalence of weight deficiency remained almost unchanged over this period, with only a slight decrease, probably because the inhabitants were mainly farm and farm/working families with better living conditions. Despite the overall increase in thinness prevalence in rural girls in Poland, different living conditions have had different biological effects.